2021
DOI: 10.3390/ma14185222
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Hysteresis Phenomena on Hydrodynamic Lubrication in a Seal-Type Thrust Bearing with Dimples

Abstract: This paper described unique hysteresis phenomena that appear in the hydrodynamic lubrication properties of dimpled thrust bearings. A seal-type thrust bearing specimen was textured with dimples. The load-carrying capacity and frictional torque were measured with a constant film thickness and compared to those of a dimple-free specimen. For examining the size of cavitation bubbles that occurred in various conditions, the lubricating area was observed during experiments. The used dimpled specimen produced the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Fig. 1 shows a schematic of the experimental apparatus used in this study [4][5]. The thrust bearing consists of an upper glass disk and a dimpled brass specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 1 shows a schematic of the experimental apparatus used in this study [4][5]. The thrust bearing consists of an upper glass disk and a dimpled brass specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 1 shows a schematic of the experimental apparatus used in this study [24][25][26]. The thrust bearing consists of an upper glass disk and a dimpled brass specimen.…”
Section: Experiments 21 Experimental Apparatusmentioning
confidence: 99%
“…To overcome this difficulty, the authors newly developed an experimental apparatus in which the frictional torque, LCC, and cavitation area ratio in the dimples could be measured while maintaining a constant oil-film thickness [24]. Using this device, the hysteresis characteristics of the LCC caused by cavitation bubbles were clarified in a previous study [25]. In addition, the measurement results using this device were compared with the experimental results under a constant load, which is considered common practice.…”
Section: Introductionmentioning
confidence: 99%
“…After that, researchers used both numerical simulations and experimental methods to study mechanical face seals with spiral grooves, T-grooves or inclined elliptical grooves [14][15][16][17][18][19][20][21]. The results showed that good dynamic pressure characteristics and friction characteristics could be obtained under the liquid lubrication condition, indicating that the structure of the inclined elliptical grooves had a better pumping effect than that of the spiral grooves.…”
Section: Introductionmentioning
confidence: 99%